A Five Immune-Related lncRNA Signature as a Prognostic Target for Glioblastoma - Li, Xiaomeng; Sun, Li; Wang, Xue; Wang, Nan; Xu, Kanghong; Jiang, Xinquan; Xu, Shuo (Frontiers in Molecular Biosciences, 2021)
Background: A variety of regulatory approaches including immune modulation have been explored as approaches to either eradicate antitumor response or induce suppressive mechanism in the glioblastoma microenvironment. Thus, the study of immune-related long noncoding RNA (lncRNA) signature is of great value in the diagnosis, treatment and prognosis of glioblastoma. Methods: Glioblastoma samples with lncRNA sequencing and corresponding clinical data were acquired from the Cancer Genome Atlas (TCGA) database. Immune-lncRNAs co-expression networks were built to identify immune-related lncRNAs via Pearson correlation. Based on the median risk score acquired in the training set, we divided the samples into high- and low-risk groups and demonstrate the survival prediction ability of the immune-related lncRNA signature. Both principal component analysis (PCA) and gene set enrichment analysis (GSEA) were used for immune state analysis. Results: A cohort of 151 glioblastoma samples and 730 immune-related genes were acquired in this study. A five immune-related lncRNA signature (AC046143.1, AC021054.1, AC080112.1, MIR222HG, and PRKCQ-AS1) was identified. Compared with patients in the high-risk group, patients in the low-risk group showed a longer overall survival (OS) in the training, validation and entire TCGA set (P=1.931e-05, P=1.706e-02 and P=3.397e-06, respectively). Additionally, the survival prediction ability of this lncRNA signature was independent of known clinical factors and molecular features. The area under ROC curve (AUC) and stratified analyses were further performed to verify its optimal survival predictive potency. Of note, the high- and low-risk groups exhibited significantly distinct immune state according to the PCA and GSEA analyses. Conclusions: Our study propose that a five immune-related lncRNA signature can be utilized as a latent indicator of prognosis and potential therapeutic approach for glioblastoma.